Analisis Dampak dan Strategi Pengendalian Kerusakan Mangrove Pesisir Sumatera Utara - Tri Girl Laurensia Simbolon; Donita Br Simanungkalit; Riska Marpaung; Frans Togu Sihombing; Abigael Putra Siallagan; Marly Meani Silalahi; Sthepany Rut Monika Lumban Tobing; Jahya Adi Putra Simbolon; Taufiq Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2024)
Mangrove forests are coastal forests where the water rises at high tide and falls at low tide. Mangroves are found in tropical and sub-tropical coastal areas in the world, including Indonesia and one of them is on the coast of North Sumatra. Mangrove forests are very important to protect because they function to protect coastlines, habitat for plants and animals, store carbon, source of food and fuel, absorb pollutants, and of course greatly help the economy of the surrounding communities. The existence of mangrove forests on the coast of North Sumatra is very concerning and has a negative impact on the environment and surrounding communities, especially local fishermen. The research method used is descriptive qualitative with literature study techniques. The purpose of this paper is to analyze the impacts and strategies for controlling mangrove damage on the coast of North Sumatera..